Human‐in‐the‐loop Control of a Humanoid Robot for Disaster Response: A Report from the DARPA Robotics Challenge Trials. Issue 2 (March 2015) - DeDonato, Mathew; Dimitrov, Velin; Du, Ruixiang; Giovacchini, Ryan; Knoedler, Kevin; Long, Xianchao; Polido, Felipe; Gennert, Michael A.; Padır, Taşkın; Feng, Siyuan; Moriguchi, Hirotaka; Whitman, Eric; et al.
<x xml:space="preserve">Abstract</x> The DARPA Robotics Challenge (DRC) requires teams to integrate mobility, manipulation, and perception to accomplish several disaster‐response tasks. We describe our hardware choices and software architecture, which enable human‐in‐the‐loop control of a 28 degree‐of‐freedom Atlas humanoid robot over a limited bandwidth link. We discuss our methods, results, and lessons learned for the DRC Trials tasks. The effectiveness of our system architecture was demonstrated as the WPI‐CMU DRC Team scored 11 out of a possible 32 points, ranked seventh (out of 16) at the DRC Trials, and was selected as a finalist for the DRC Finals.